Interpreting interpretivism interpreting interpretations: The new hermeneutics of public administration - Hay, Colin (2011)
This article seeks to gauge the nature, distinctiveness and significance of the `interpretivist turn' in public administration and political science more broadly. It considers the various interpretations and, indeed, misinterpretations to which this new hermeneutics of public administration has given rise, its relationship to (genuinely and seemingly) cognate perspectives (notably constructivism, the new institutionalism and critical realism) and its strengths and weaknesses - both as an analytical perspective and as a developing research programme. In the process it argues for a broadening of the interpretivist research agenda to accord a greater role to the institutional contexts in which the ideas and belief that actors hold acquire and retain resonance and for the value of exploring more thoroughly the synergies with constructivist variants of the new institutionalism. - Reproduced.
Keywords: Public administration